2010
DOI: 10.1089/dna.2009.0978
|View full text |Cite
|
Sign up to set email alerts
|

Radiation-Induced Micro-RNA Modulation in Glioblastoma Cells Differing in DNA-Repair Pathways

Abstract: Human glioblastomas often develop resistance to radiation therapy. The molecular details of this phenomenon are not completely understood. Recent studies have suggested that deficiency in DNA repair pathways may alter the resistance to ionizing radiation in gliobastomas. The human glioma cell line M059J is deficient in DNA-dependent protein kinase (DNA-PK), whereas cell line M059K, isolated from the same malignant tumor, has normal DNA-PK activity. DNA-PK plays a central role in the repair of ionizing-radiatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
81
0
3

Year Published

2013
2013
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 119 publications
(90 citation statements)
references
References 40 publications
(44 reference statements)
6
81
0
3
Order By: Relevance
“…However, research on the relationship between miR‐19 and radiotherapy in glioma is limited. Chaudhry has reported that miR‐19 is up‐regulated in both irradiated glioma cell line M059J which is deficient in DNA‐PK (DNA‐dependent protein kinase) and glioma cell line M059K with normal DNA‐PK activity, indicating that miR‐19 paritcipates in the reaction of different types of glioma cell lines to ionizing radiation 63. Some of the target genes of miR‐19 are related to the radiosensitivity of glioma cells.…”
Section: Mir‐19 and Treatment Of Gliomamentioning
confidence: 99%
“…However, research on the relationship between miR‐19 and radiotherapy in glioma is limited. Chaudhry has reported that miR‐19 is up‐regulated in both irradiated glioma cell line M059J which is deficient in DNA‐PK (DNA‐dependent protein kinase) and glioma cell line M059K with normal DNA‐PK activity, indicating that miR‐19 paritcipates in the reaction of different types of glioma cell lines to ionizing radiation 63. Some of the target genes of miR‐19 are related to the radiosensitivity of glioma cells.…”
Section: Mir‐19 and Treatment Of Gliomamentioning
confidence: 99%
“…Significantly, certain miRNAs have been identified to consistently show characteristic changes postirradiation across a range of different cancers. For example, expression of several members of the let-7 family, a well-known tumor suppressor and regulator of the K-Ras oncogene, were found to be affected by radiation exposure (29,30,(32)(33)(34)(35). Most members of the let-7 family (except let-7g) have been found to be downregulated in irradiated fibroblasts (33), lung cancer cells (30) or colon cancer cells (35).…”
Section: Mirnas To Monitor Response To Radiotherapymentioning
confidence: 99%
“…Most members of the let-7 family (except let-7g) have been found to be downregulated in irradiated fibroblasts (33), lung cancer cells (30) or colon cancer cells (35). However, in irradiated glioma and squamous cell carcinoma cell lines REVIEW some members of the let-7 family are upregulated (29,34). Another two miRNAs, miR-21 and miR-34, are consistently upregulated in various benign and malignant cell lines after irradiation (28, 34, 36-38).…”
Section: Mirnas To Monitor Response To Radiotherapymentioning
confidence: 99%
“…This published finding inspired the search for other radiation-responsive miRNAs (19)(20)(21)(22). The radiation-induced miRNA response depends on radiation dose, time post exposure, genetic background (23)(24)(25)(26), the tissue being investigated and gender (27)(28)(29).…”
Section: Introductionmentioning
confidence: 99%